X-linked alpha-thalassemia/mental retardation (ATR-X) syndrome: localization to Xq12-q21.31 by X inactivation and linkage analysis. - Gibbons, R; Suthers, G; Wilkie, A; Buckle, V; Higgs, D (1992)
We have examined seven pedigrees that include individuals with a recently described X-linked form of severe mental retardation associated with alpha-thalassemia (ATR-X syndrome). Using hematologic and molecular approaches, we have shown that intellectually normal female carriers of this syndrome may be identified by the presence of rare cells containing HbH inclusions in their peripheral blood and by an extremely skewed pattern of X inactivation seen in cells from a variety of tissues. Linkage analysis has localized the ATR-X locus to an interval of approximately 11 cM between the loci DXS106 and DXYS1X (Xq12-q21.31), with a peak LOD score of 5.4 (recombination fraction of 0) at DXS72. These findings provide the basis for genetic counseling, assessment of carrier risk, and prenatal diagnosis of the ATR-X syndrome. Furthermore, they represent an important step in developing strategies to understand how the mutant ATR-X allele causes mental handicap, dysmorphism, and down-regulation of the alpha-globin genes.